INTEGRASI HISAB RUKYAT AWAL RAMADAN 1442 H DENGAN MODEL VISIBILITAS KASTNER - sakirman, sakirman; Utama, Judhistira Aria; Zainon, Othman bin (ELFALAKY: Jurnal Ilmu Falak, 2022)
There is no empirical evidence of the early hilal of Ramadan 1442 H that was observed through technological devices. The justification for witnessing the new moon still refers to the syar'i new moon term, not the astronomical new moon. The country of Brunei Darussalam can be used as an example when the astronomical hilal is not successfully observed, then the beginning of the hijri month is the next day or fulfills the ongoing month and there is no legal tolerance such as the use of the syar'i hilal term to replace the astronomical hilal. The integration of reckoning-rukyat is actually a methodological endeavor to perfect the criteria for the beginning of the Hijri month. Kastner's hilal visibility model is present in an effort to bridge the refinement of the criteria for the beginning of the hijri month. Through the criteria for the visibility of the hilal, Kastner offers a mathematical model that can be used as a role model for observing the hilal. Kastner's hilal visibility mathematical calculation model can be expressed in a curve that can be translated easily. Based on Kastner's hilal visibility, the early hilal of Ramadan 1442 H the hilal cannot be observed with the visual eye. Perukyat's testimony of seeing the hilal at the beginning of Ramadan 1442 H can be rejected by law because it is not based on empirical evidence in the form of a hilal image as a result of visual eye observation. According to Kasnter's hilal visibility model, the visibility of the hilal at the beginning of Ramadan 1442 H reached the maximum hilal visibility with a value of -1.68 for visual observations, the height of the hilal at the same time was 1.56 degrees (height difference between the Moon and the Sun at that time was 4, 46 degrees) with an elongation of 4.70 degrees. Observing the new moon without using tools such as a telescope, will not succeed in detecting the figure of the new moon, because the visibility of the new moon is still negative since sunset.